The Congolese National Police subculture and smudge in Kisangani town - Emmanuel Imbwatcheke Bofonga; Jean Losumbe Bondondo (IJRDO - Journal of Social Science and Humanities Research, 2019)
The professional culture of an organizationmakes, for a large side, the dividualspersonalitywhichmakesthemapartsincethispersonalityis the product of a long experiencesacquisiredtogetherwithin the sameorganization. So throughresearchescarried out in Congolese National Police (CNP) services in Kisangani. The followingresearchpaperinterds to reveal the CNP subculture and its impact on phenomenon of CNPsmudge. In clearword, itshouldbebetter to show how this subculture predisposes the policemen whoperpetrateregularly the smudgeacts, and the subculture issopposed to preferthat one of culture for normal isolation, the CNP professional and society. However, the research has shownthatmore than six components of this subculture seem to be shore by a greatnumber of policemen of Kisangani : the policemen attachmenton ranks and military switch code, excessive dependance of alcohol and drug (narcotic), the attribution of bellicositicalnicknames, confident and mutualsolidarity, the policing pragmatics and autorization, tendence to besupplied by citizens. So, it has been determinedthatearch one of the six components effectivelypredisposed the policemen who commit thesesmudgeacts. There is a kind "socialization of the policemen in culture of smudge", ratherthanlegitimate violence. In addition, itishighlyshownthat six components are supplementary and interconnectable eachother, and form a wholecalled "the professional subculture of the policemen of Kisangani", whichmakesthe entrency of theselater in the profession and push people to qualifythem "the policemen of smudge". As remedies, the policemen shouldberesocialized to the democratic culture and humain respect on providingthen the best conditions of duty.